2020
DOI: 10.1007/s00167-020-06362-1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic calcaneoplasty for the treatment of Haglund’s deformity provides better clinical functional outcomes, lower complication rate, and shorter recovery time compared to open procedures: a systematic review

Abstract: Purpose The aim of this research is to report the clinical outcome following surgical correction of Haglund's deformity summarising diferent surgical strategies and comparing clinical outcomes, failures, complications and return to activities of patients underwent open and endoscopic techniques. Methods A systematic search of the literature was conducted using eight diferent databases. Thirty-ive studies were included in the systematic review. A total of 1260 ankles of 1147 patients were grouped in accordance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
(231 reference statements)
1
10
0
Order By: Relevance
“…Finally, there were no postoperative complications in any of the 24 endoscopic surgeries performed: no Achilles tendon rupture, dehiscence, or sign of Achilles tendon infection were identified, either in the immediate postoperative period or in a period of 18 to 36 months after the procedure. These data are in line with findings described in the literature, as other studies have shown good outcomes in terms of improvement of both pain and function (14,16,19) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, there were no postoperative complications in any of the 24 endoscopic surgeries performed: no Achilles tendon rupture, dehiscence, or sign of Achilles tendon infection were identified, either in the immediate postoperative period or in a period of 18 to 36 months after the procedure. These data are in line with findings described in the literature, as other studies have shown good outcomes in terms of improvement of both pain and function (14,16,19) .…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study are consistent with those of a systematic review published in November 2020 by the European Society for Sports Traumatology, Knee Surgery and Arthroscopy (ESSKA), which found that the correction of Haglund deformity provides a good clinical status and a low complication rate. The endoscopic approach ensures significantly better postoperative AOFAS scores and a faster return to daily activities when compared to open surgery (19) . Finally, there were no postoperative complications in any of the 24 endoscopic surgeries performed: no Achilles tendon rupture, dehiscence, or sign of Achilles tendon infection were identified, either in the immediate postoperative period or in a period of 18 to 36 months after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Current reports discuss endoscopic Haglund deformity resection as a surgical technique for pathologies associated with Achilles tendon insertion. 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 This method involves an endoscopic dissection of the soft tissue surrounding the Haglund deformity and resection of the bone. 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 However, it should be noted that this technique was entirely different from our technique.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 This method involves an endoscopic dissection of the soft tissue surrounding the Haglund deformity and resection of the bone. 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 However, it should be noted that this technique was entirely different from our technique. Endoscopic Haglund deformity resection has been reported only for Haglund’s disease; no report has discussed the use of endoscopic Haglund deformity resection alone for insertional Achilles tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we included 12 studies [8,[26][27][28][29][30][31][32][33][34][35][36] where only study was systematic review [29] . The pooled studies included 1542 patients with Haglund's symptom with mean age 41.98 years old (Standard deviation of 7.1 years, minimum and maximum age of 32.5 and 59.3 years old).…”
Section: General Characteristics Of the Studiesmentioning
confidence: 99%